Site Investigation Using Resistivity Imaging - Hossain, Sahadat; Khan, Sadik; Kibria, Golam (Milton : Chapman and Hall/CRC, 2018)
Subsurface investigation is the most important phase of any civil engineering construction or development activities. The geologic conditions can be extremely complex, variable, and subject to change with time; soil test borings and in-situ tests are employed to obtain subsoil information. Resistivity Imaging (RI) is a non-destructive, fast and cost-effective method of site investigation and soil characterization. Site Investigation using Resistivity Imaging aims to summarize pertinent details of RI in site investigation for geotechnical and geo-environmental applications. It aims to bridge the gap that currently exists between the geotechnical/geo-environmental and geophysical engineering community. The geotechnical and geo-environmental engineers will be able to interpret the geophysical data and utilize the information for their design. It will be a comprehensive handbook for the application of RI in geotechnical and geo-environmental site investigations.
4.4.4 Evaluation of undisturbed clay properties using the Kibria and Hossain (2016) model4.4.5 Limitations of the Kibria and Hossain models (2015 and 2016); 4.4.6 Evaluation of corrosion potential (Kibria and Hossain, 2017); 5 Electrical resistivity of municipal solid waste (MSW); 5.1 General; 5.2 Effect of moisture content on electrical resistivity; 5.2.1 Fresh MSW samples; 5.2.2 Landfilled MSW samples; 5.2.3 Degraded MSW samples; 5.3 Effect of unit weight; 5.3.1 Fresh MSW samples; 5.3.2 Landfilled MSW samples; 5.3.3 Degraded MSW samples; 5.4 Effect of decomposition
Description based upon print version of record.
5.5 Effect of temperature
OCLC-licensed vendor bibliographic record.
Keywords: TECHNOLOGY & ENGINEERING / Construction / General; TECHNOLOGY & ENGINEERING / Civil / General; Geotechnical engineering -- Technique; Earth resistance (Geophysics) -- Measurement; Soils -- Analysis -- Technique; Electrical impedance tomography; Engineering geology